Die Haut auf dem Markte: Betrieblicher Gesundheitsschutz im Marktkapitalismus - Becker, Karina; Brinkmann, Ulrich; Engel, Thomas (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2007)
Employees’ health is a historically continuous object of exchange processes in capitalist formations. Even after establishing high standards of safety at work and health protection in the fordist age there are ongoing bargains with the commodity of labour including the implicit selling of health. The "shifting of market boundaries" is an explanatory approach analyzing the current changes of this bartering process. Instead of describing it as a one way perspective of anonymous "marketization" we stress the perspective of internal and external actors who are not determined by structures but who are involved in bargaining processes resulting in changes of markets as a mode of social coordination. Thus practice of resistance with regards to safety at work and health protection will be understandable.